Diagnostic accuracy of shear wave elastography for prediction of breast malignancy in patients with pathological nipple discharge. Issue 1 (22nd January 2016) - Guo, Xiaobo; Liu, Ying; Li, Wanhu
Abstract : Objectives: Pathological nipple discharge (PND) may indicate malignant breast lesions. As the role of shear wave elastography (SWE) in predicting these malignant lesions has not yet been evaluated, we aim to evaluate the diagnostic value of SWE for this condition. Design: Prospective diagnostic accuracy study comparing a combination of qualitative and quantitative measurements of SWE (index test) to a ductoscopy and microdochectomy for histological diagnosis (reference test). Setting: Fuzhou General Hospital of Nanjing military command. Participants: A total of 379 patients with PND were finally included from January, 2011 to March 2014, after we screened 1084 possible candidates. All participants were evaluated through SWE, with qualitative parameters generated by Virtual Touch tissue imaging (VTI) and quantitative parameters generated by Virtual Touch tissue quantification (VTQ). All the patients were consented to receive a ductoscopy and microdochectomy for histological diagnosis, and the results were set as a reference test. Outcome measures: Sensitivity and specificity of the combined VTI and VTQ of the SWE for detection of malignancy in patients with PND. Results: The 379 participants presented with 404 lesions. The results of pathological examination showed that 326 (80.7%) of the 404 lesions were benign and the other 78 (19.3%) were malignant. An area under the curve of elasticity score, VTQm and VTQc, were 0.872, 0.825 and 0.857, respectively, with the corresponding cut-off point as 2.50, 2.860 m/s and 3.015 m/s, respectively. After a combination of these measurements, the sensitivity, specificity, and positive and negative predictive value (PPV and NPV), were 89.7%, 72.1%, 43.5% and 96.7%, respectively. The sensitivity analysis showed 82% of the sensitivity and 96.8% of the specificity, in which patients with no pathological findings in ductoscopy were excluded. Conclusions: Ultrasonographic elastography is sensitive for patients with PND and could be used as a triage test before ductoscopy examination. Studies for further improvement of diagnostic sensitivity are warranted.